Discovery, Structure Elucidation, and Biological Characterization of Nannocystin A, a Macrocyclic Myxobacterial Metabolite with Potent Antiproliferative Properties1. (1st June 2015) - Hoffmann, Holger; Kogler, Herbert; Heyse, Winfried; Matter, Hans; Caspers, Michael; Schummer, Dietmar; Klemke‐Jahn, Christine; Bauer, Armin; Penarier, Geraldine; Debussche, Laurent; Brönstrup, Mark
Abstract Microbial natural products are a rich source of bioactive molecules to serve as drug leads and/or biological tools. We investigated a little‐explored myxobacterial genus, Nannocystis sp., and discovered a novel 21‐membered macrocyclic scaffold that is composed of a tripeptide and a polyketide part with an epoxyamide moiety. The relative and absolute configurations of the nine stereocenters was determined by NMR spectroscopy, molecular dynamics calculations, chemical degradation, and X‐ray crystallography. The compound, named nannocystin A (1), was found to inhibit cell proliferation at low nanomolar concentrations through the early induction of apoptosis. The mode of action of 1 could not be matched to that of standard drugs by transcriptional profiling and biochemical experiments. An initial investigation of the structure–activity relationship based on seven analogues demonstrated the importance of the epoxide moiety for high activity.